The Passive as an Impersonalisation Strategy in Afrikaans and Dutch: A Corpus Investigation - Breed, Adri; Van Olmen, Daniël (Dutch crossing, 2021)
Although a lot of research has been done on the use of pronouns to express impersonal meaning in West Germanic languages, relatively little is known about the use of other possible impersonalization strategies. This article therefore examines the agentless passive as a possible impersonalizing strategy in Afrikaans and Dutch. On the basis of corpus data, we show that the agentless passive is a productive strategy for impersonalization in both Afrikaans and Dutch -in that it is used in the entire range of impersonal contexts. However, it is more typically employed for corporate contexts and existential contexts where the subject is vague and number-neutral. Some variation in the use of the agentless passive in different genres are also seen. On the whole, however, the agentless passives behave very similarly in the two languages as an impersonalizing strategy.